The pathology of eclampsia: An autopsy series - Jonathan L. Hecht; Jaume Ordi; Carla Carrilho; Mamudo R. Ismail; Zsuzsanna K. Zsengeller; S. Ananth Karumanchi; Seymour Rosen (Taylor & Francis Group, 2017)
Objective: We describe the main lesions in the liver, brain, and kidney from autopsies of women who died of eclampsia and characterize the endothelial injury. Methods: Cases were identified from a study involving 317 maternal deaths (2003-2006) conducted at the Maputo Central Hospital (Maputo, Mozambique) in association with ISGlobal (Barcelona, Spain). Histology slides along with stains for endothelial, histiocyte, and platelet markers (CD31, CD34, CD68, CD42B) were reviewed to identify the relevant lesions. Malondialdehyde stain was performed to demonstrate free radical generation. Results: Brain lesions were characterized by perivascular "edema" (68.4%), hemorrhage (36.8%), hemosiderin (31.6%), small vessel thrombosis (10.5%), and parenchymal necrosis (15.8%). Liver sections showed periportal/portal necrosis and sinusoidal fibrin (72.2%) with associated hepatic arterial medial necrosis (44.4%). Kidneys showed glomerular endotheliosis. Endothelial, histiocytic, and platelet markers highlighted capillary injury in the otherwise intact brain parenchyma. Stains for free radical formation were positive predominantly in the areas of tissue injury, but intact glial/neuronal elements were focally positive as evidence of widespread oxidative stress. Conclusion: Pathological changes in cases of eclampsia include widespread endothelial/vascular injury in vulnerable organ beds.